Genetic differentiation of selected drought and heat tolerant wheat genotypes using simple sequence repeat markers and agronomic traits. Issue 3 (26th May 2020) - Mkhabela, Sonto Silindile; Shimelis, Hussein; Mashilo, Jacob
Abstract : Development of wheat ( Triticum aestivum L.) varieties with increased yield potentials that are adapted to drought and heat stresses requires genetically differentiated and complementary parents. The present study established genetic profiles of heat and drought tolerant wheat genotypes through SSR loci and agronomic traits for breeding. Fourteen candidate wheat genotypes selected from the International Maize and Wheat Improvement Centre (CIMMYT) and a local variety were genotyped using 10 diagnostic SSR markers. Further, the genotypes were evaluated for agronomic performance under non-stressed (NS) and drought-stressed (DS) conditions. The mean gene diversity of 0.75 confirmed genetic diversity of evaluated wheat genotypes. Analysis of molecular variance accounted for 75 and 25% of the variation within and among genotypes respectively. Significant differences were observed for assessed agronomic traits under NS and DS conditions. There were significant ( p < 0.01) correlations between grain yield and plant height ( r = -0.42) and spike length ( r = 0.39) under DS conditions. Cluster analysis allocated test genotypes to three genetic groups and aided selection of genetically unrelated and high-yielding heat and drought tolerant genotypes such as SM04, SM19 and SM32. These are useful germplasm for developing breeding populations for improved yield gains.